Effectiveness of Facial Acupressure and Acupuncture on Musculus Facei - Ayly Soekanto; Putu Oky Ari Tania; Emillia Devi Dwi Rianti; Hardiyono Hardiyono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Fatigue on the face can affect the brightness of the face, if the facial muscles function well, the health of the face will be immediately visible. There are many facial care methods currently offered, which can be done with facial acupuncture and acupuncture. This study aims to determine the effectiveness of facial acupressure and acupuncture on the facial muscles, which has never been done before. Methods: Analytical experimental research was divided into two groups, the first group was given facial acupuncture treatment and the second group was given facial acupuncture treatment. The data obtained in the form of facial muscle relaxation is indicated by the disappearance of wrinkles on the face with a score of (1, 2, 3). The dependent variables are facial acupuncture and facial acupuncture. Inclusion criteria were women aged 40 – 50 years, agreed to take part in this study, and had no facial abnormalities. The exclusion criteria are women aged less than 40 years or over 50 years, and there are defects in the facial area. This research will be carried out in May – June 2023 at the Wijaya Surabaya doctor's practice and polyclinic. Results: The results of the study found that 20 minutes of facial acupuncture was useful for relaxing the facial muscles by up to 60%, on the sixth day the face looked brighter and cleaner, while acupuncture therapy on the facial muscles experienced relaxation of up to 60% on the sixth day with 30 minutes. The effectiveness of facial acupressure therapy is 10 minutes faster than acupuncture. Conclusion: Facial acupressure therapy and acupuncture therapy have proven to be effective in relaxing the facial muscles.